SOCIAL ENGINEERING AS AN EVOLUTIONARY THREAT TO INFORMATION SECURITY IN HEALTHCARE ORGANIZATIONS - Naiya Patel (Indonesian Journal of Health Administration, 2020)
Information security in healthcare settings is overlooked even though it is the most vulnerable for social engineering attacks. The theft of hospital information data is critical to be monitored as they contain patients’ confidential health information. If leaked, the data can impact patients’ social as well as professional life. The hospital data system includes administrative data, as well as employees’ personal information hacked, which can cause identity theft. The current paper discusses types and sources of social engineering attacks in healthcare organizations. Social engineering attacks occur more frequently than other malware attacks, and hence it is crucial to understand what social engineering is and its vulnerabilities to understand the prevention measures. The paper describes types of threats, potential vulnerabilities, and possible solutions to prevent social engineering attacks in healthcare organizations. Keywords: social engineering, hospitals, healthcare organizations, information security.